Aberrant Functional and Causal Connectivity in Acute Tinnitus With Sensorineural Hearing Loss - Cai, Yuexin; Xie, Mingwei; Su, Yun; Tong, Zhaopeng; Wu, Xiaoyan; Xu, Wenchao; Li, Jiahong; Zhao, Fei; Dang, Caiping; Chen, Guisheng; Lan, Liping; Shen, Jun; et al. (Frontiers in Neuroscience, 2020)
Purpose: The neural bases in acute tinnitus remains largely undetected. The objective of this study was to identify the alteration of brain network involved in patients with acute tinnitus and hearing loss. Methods: Acute tinnitus patients (n=24) with hearing loss and age-, sex-, education- matched healthy controls (n=21) participated in the current study and underwent the resting-state functional magnetic resonance imaging (fMRI) scanning. ReHo and ALFF was used to investigate the local spontaneous neural activity, functional connectivity (FC) and Granger causality analysis (GCA) was used to analyze the undirected and directed connectivity of brain regions. Results: Compared with healthy subjects, acute tinnitus patients had a general reduction in FC between auditory and non-auditory regions. Based on FC analysis, the superior temporal gyrus (STG) revealed reduced undirected connectivity with non-auditory regions including amygdala (AMYG), nucleus acccumbens (NAc), cerebellum and postcentral gyrus (PoCG). With CGA algorithm, increased effective connectivity from the right AMYG to the right STG and reduced connectivity from the right PoCG to the left NAc was observed in acute tinnitus patients with hearing loss. Puretone threshold was positively correlated with FC between AMYG and STG, and negatively correlated with FC between the left NAc and the right PoCG. In addition, a negative association between the GCA value from right PoCG to the left NAc and the THI scores was observed. Conclusion: Acute tinnitus patients have aberrant FC strength and causal connectivity in both auditory and non-auditory cortex, especially in the STG, AMYG and NAc. The current findings will provide a new perspective for understanding the neuropathophysiological mechanism in acute tinnitus.